1997
DOI: 10.1093/oxfordjournals.aje.a009061
|View full text |Cite
|
Sign up to set email alerts
|

Low Cord Blood Pneumococcal Immunoglobulin G (IgG) Antibodies Predict Early Onset Acute Otitis Media in Infancy

Abstract: Low maternally derived serum immunoglobulin G (IgG) antibodies to Streptococcus pneumoniae capsular polysaccharides (PS) combined with the inability of infants to produce anti-PS antibody may explain onset of otitis media in the first 6 months of life. To explore this relation, cord blood samples were assayed for anti-PS IgG antibodies from 414 of 592 infants enrolled in a study of early onset otitis media between 1991 and 1994. Infants' ears were examined at health supervision and illness visits for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
2
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
0
26
2
3
Order By: Relevance
“…A literatura tem mostrado que, das manifestações otorrinolaringológicas, as otites média, aguda ou crônica são as principais queixas das crianças relacionadas à exposição ambiental do cigarro (21,24,(39)(40)(41) . É importante salientar que o critério adotado neste estudo foi um diagnóstico "referido" e, para maior confiabilidade, foi decidido que apenas os casos confirmados por médicos seriam considerados como portadores da doença.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A literatura tem mostrado que, das manifestações otorrinolaringológicas, as otites média, aguda ou crônica são as principais queixas das crianças relacionadas à exposição ambiental do cigarro (21,24,(39)(40)(41) . É importante salientar que o critério adotado neste estudo foi um diagnóstico "referido" e, para maior confiabilidade, foi decidido que apenas os casos confirmados por médicos seriam considerados como portadores da doença.…”
Section: Discussionunclassified
“…Cinco estudos recentes realizados, respectivamente, no Canadá (21) , Suécia (22) , Malásia (23) e EUA (Minnesota (24) e Pensilvânia (25) ), apresentaram dados mostrando associação entre otite média, aguda ou crônica e fumo dos pais.…”
Section: Introductionunclassified
“…A pneumococcal polysaccharide vaccine given during pregnancy could induce protecting antibodies detectable in the newborn for some months [56][57][58]. This approach might be of value in trying to prevent early-onset AOM, which possibly may trigger a child to have recurrent attacks of AOM [59].…”
Section: Passive Immunoprophylaxismentioning
confidence: 99%
“…One reported that adjustment had the effect of increasing the excess risk, but the opposite effect was reported by another, although it should be noted that the adjusted relative risks in this study [31] were presented for two separate age groups, while the unadjusted relative risk was based on the two age groups combined. The failure of the 3 other studies [14,36,46] which presented adjusted relative risks to give AOM = Acute otitis media; ROM = recurrent otitis media; OME = otitis media with effusion; POME = persistent otitis media with effusion; UMED = unspecified middle ear disease.…”
Section: Index Of Exposurementioning
confidence: 99%
“…Three studies [6,8,15] stated that parental smoking habits were recorded at the beginning of the study period only, 4 studies [4,33,40,53] recorded parental smoking habits at the end of the study period only, 1 study [43] collected information at the beginning or at the end of the study only, 1 study [32] collected information at the beginning of the study or at the birth of the child, while in 5 other studies [12,22,35,51,56], the time at which the information was collected was not stated. The remaining studies [10,13,18,21,24,27,34,46,47,55,58] recorded parental smoking habits throughout the study period.…”
Section: Misclassification Of Exposurementioning
confidence: 99%